2009
DOI: 10.1086/644601
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidium parvumInfection Rapidly Induces a Protective Innate Immune Response Involving Type I Interferon

Abstract: Type II interferon (IFN), IFN-gamma, is important in innate immunity to the intestinal protozoan parasite Cryptosporidium species, which infects epithelial cells (enterocytes). This investigation is, to our knowledge, the first to characterize the role of type I IFN in innate immunity to this parasite. Pretreatment of human or murine enterocyte cell lines with IFN-alpha/beta inhibited parasite development, and we identified that a key mechanism of cytokine action was to prevent parasite invasion of enterocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 26 publications
1
62
0
Order By: Relevance
“…The invasion of intestinal and biliary epithelial cells by C. parvum in vitro activates epithelial cells, resulting in the production and secretion of various cytokines and chemokines and anti-microbial peptides (e.g., β-defensins and cathelicidins) that can kill C. parvum or inhibit parasite growth (Chen et al, 2005; Ehigiator et al 2005; Barakat et al, 2009). MyD88-deficient mice and IFN-γ- or TNF-α-deficient mice are more sensitive to C. parvum infection (Lacroix et al, 2001; Rogers et al, 2006), and acquired resistance to cryptosporidial infection is dependent upon T-cells (McDonald et al, 2000; Deng et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The invasion of intestinal and biliary epithelial cells by C. parvum in vitro activates epithelial cells, resulting in the production and secretion of various cytokines and chemokines and anti-microbial peptides (e.g., β-defensins and cathelicidins) that can kill C. parvum or inhibit parasite growth (Chen et al, 2005; Ehigiator et al 2005; Barakat et al, 2009). MyD88-deficient mice and IFN-γ- or TNF-α-deficient mice are more sensitive to C. parvum infection (Lacroix et al, 2001; Rogers et al, 2006), and acquired resistance to cryptosporidial infection is dependent upon T-cells (McDonald et al, 2000; Deng et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…23 The development of C. parvum infection in intestinal epithelial cells is effectively controlled by both type I and type II IFNs. 32,33 We observed that the injection of poly(I:C) into infected IFN-αRand IFN-γ-deficient neonatal mice did not reduce the parasite load in the intestines. 23 Unlike type I IFNs, IFN-γ affects the invasion of enterocytes by C. parvum by decreasing the amount of cellular Fe 2+ available.…”
Section: The Role Of Poly(i:c) In the Stimulation Of Innate Immune Rementioning
confidence: 88%
“…23 Unlike type I IFNs, IFN-γ affects the invasion of enterocytes by C. parvum by decreasing the amount of cellular Fe 2+ available. 32,33 These different mechanisms of protection mediated by IFNs suggest synergy between these molecules in the control of parasite development. Type I and II IFNs bind to IFN-αR1-R2 and IFN-γR1-R2, respectively, but both induce the formation of Stat1-Stat1 homodimers, which are translocated to the nucleus, where they bind GAS (an IFN-γ-activated site) elements, thereby inducing gene transcription.…”
Section: The Role Of Poly(i:c) In the Stimulation Of Innate Immune Rementioning
confidence: 99%
“…Dendritic cells migrate toward areas of C. parvum infection in an IFN- γ-dependent manner (38), but until recently, their role in clearance of the parasite was unclear. In vitro studies found that bone marrow-derived dendritic cells challenged with C. parvum sporozoites or antigens secreted a number of cytokines, including type I IFN, TNF-α, IL-6, IL-1β, IL-12, and IL-18 (36,56,59). More recent studies have elucidated the importance of dendritic cells in vivo .…”
Section: Immune Responses To Cryptosporidiummentioning
confidence: 99%